Pricing Floating-Rate Debt and Related Interest Rate Options - Scott, Louis (IMF Working Papers; Working Paper ;, 1990)
Most developing country debt is denominated in U.S. dollars and has a floating interest rate. The pricing of floating rate debt and related interest rate options are examined in this paper. Formulas for pricing ceilings and floors on floating rate debt are derived for several different models of interest rate variability. A framework for pricing risky debt and loan guarantees is presented, and the implications of the debtor country's default option are analyzed. The elimination of large principal repayments, by collateralizing the principal, serves to reduce the debtor country's incentive to use its default option.